Engineering heterostructured grains to enhance strength in a single-phase high-entropy alloy with maintained ductility. Issue 11 (2nd November 2018) - Fu, Zhiqiang; MacDonald, Benjamin E.; Li, Zhiming; Jiang, Zhenfei; Chen, Weiping; Zhou, Yizhang; Lavernia, Enrique J.
ABSTRACT: Coarse-grained (CG) single-phase face-centered cubic (fcc) high-entropy alloys (HEAs) normally show insufficient room temperature strength. Here we design and implement a heterogeneous grain structure to strengthen a single-phase fcc Fe29 Ni29 Co28 Cu7 Ti7 HEA. Significantly, the heterostructured (HS) fcc HEA shows a dramatic enhancement (increasing from ∼350 to ∼614 MPa) in tensile yield strength as compared to its CG counterpart. As a result of its extraordinary work-hardening ability arising from the heterogeneous grain structure, the novel HS HEA exhibits a very high ultimate strength of ∼1308 MPa, and a good ductility of ∼23.1% which is almost identical to that of its CG counterpart. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Introducing a heterogeneous grain structure to a soft fcc Fe29 Ni29 Co28 Cu7 Ti7 HEA, the heterostructured HEA shows significantly enhanced strengths at an essentially identical ductility as compared to the CG counterpart.